DESIGNING INVENTORY INFORMATION SYSTEM AT PT HAADI WAHANA JAYA DESKTOP BASED - Syuhardi, Yossi Indrawati; Prastomo, Andi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This research documents the implementation process of a desktop-based inventory information system at PT Haadi Wahana Jaya with the aim of increasing the efficiency and accuracy of inventory management. Through a research and development approach, this system is designed to meet the company's specific needs. With an intuitive user interface design, the system provides easy access and navigation for users. The login form allows users to access inventory information securely, with the implementation of additional security features such as CAPTCHA. In addition, integration with financial and production systems ensures interdepartmental connectivity and better coordination. Implementation results show increased operational efficiency, optimization of inventory levels, and accurate real-time reporting. Although some challenges in terms of culture change were encountered, user feedback indicated a higher level of satisfaction. The conclusion of this research underlines the positive contribution of desktop-based inventory information systems to PT Haadi Wahana Jaya's inventory management.